2021
DOI: 10.1093/jn/nxab321
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Profiling Reveals Distinct Signatures in Undernourished Children with Environmental Enteric Dysfunction

Abstract: Background Intestinal inflammation and malabsorption in environmental enteric dysfunction (EED) are associated with early childhood growth faltering in impoverished settings worldwide. Objectives The goal of this study was to identify candidate biomarkers associated with inflammation, EED histology, and as predictors of later growth outcomes by focusing on the liver-gut axis by investigating the bile acid metabolome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
6
17
0
Order By: Relevance
“… 62 A sub-clinical cholestasis was present in malnourished Pakistani infants aged 3–9 months; this study also identified the primary conjugated bile acid glycocholic acid, but not its unconjugated metabolite cholic acid, as a marker predicting growth faltering. 63 Similarly, we found high proportions of primary conjugated bile acid substrates of BSH and low proportions of unconjugated products of BSH to be associated with lower head circumference, weight, and length velocities in preterm neonatal development. The potential role of these bile acids and BSH genes as predictive biomarkers must be validated in a larger independent cohort, and a potential growth-promoting causal role of these bile acids should be explored in preclinical models.…”
Section: Discussionsupporting
confidence: 56%
“… 62 A sub-clinical cholestasis was present in malnourished Pakistani infants aged 3–9 months; this study also identified the primary conjugated bile acid glycocholic acid, but not its unconjugated metabolite cholic acid, as a marker predicting growth faltering. 63 Similarly, we found high proportions of primary conjugated bile acid substrates of BSH and low proportions of unconjugated products of BSH to be associated with lower head circumference, weight, and length velocities in preterm neonatal development. The potential role of these bile acids and BSH genes as predictive biomarkers must be validated in a larger independent cohort, and a potential growth-promoting causal role of these bile acids should be explored in preclinical models.…”
Section: Discussionsupporting
confidence: 56%
“…Recent data in duodenal biopsies from EED children from Pakistan (32,33) show changes in lipid absorption and metabolism pathways as well as changes in duodenal and serum bile acid profiles and signals for dysbiosis (i.e., up-regulation of DUOX2) and fecal energy loss. Most interestingly, fecal energy loss and inflammation partially improved in children in a randomized control trial testing alanyl-glutamine as a gut repair nutrient for an intervention of 10 days (34).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also assess for blood lipid profiles and spot fecal fat or calorimetry in fecal samples to assess for lipid status directly in the affected children and strengthen the link between small intestinal microbial shifts, lipid malabsorption, and EED. Recent data in duodenal biopsies from EED children from Pakistan ( 32 , 33 ) show changes in lipid absorption and metabolism pathways as well as changes in duodenal and serum bile acid profiles and signals for dysbiosis (i.e., up-regulation of DUOX2) and fecal energy loss. Most interestingly, fecal energy loss and inflammation partially improved in children in a randomized control trial testing alanyl-glutamine as a gut repair nutrient for an intervention of 10 days ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…7α-hydroxy-4-cholesten-3-one (7α-C4) was measured in plasma using a stable-isotope dilution LC-MS/MS assay as previously reported [ 15 ].…”
Section: Methodsmentioning
confidence: 99%